Xenografting of human fetal testis tissue: a new approach to study fetal testis development and germ cell differentiation - Mitchell, Rod T. (Oxford University Press, 2010)
BACKGROUND: Abnormal fetal testis development can result in disorders of sex development (DSDs) and predispose to later testicular dysgenesis syndrome (TDS) disorders such as testicular germ cell tumours. Studies of human fetal testis development are hampered by the lack of appropriate model, and intervention systems. We hypothesized that human fetal testis xenografts can recapitulate normal development. METHODS: Human fetal testes (at 9 weeks, n = 4 and 14–18 weeks gestation, n = 6) were xenografted into male nude mice for 6 weeks, with or without hCG treatment of the host, and evaluated for normal cellular development and function using immunohistochemistry, triple immunofluorescence and testosterone assay. The differentiation and proliferation status of germ cells within xenografts was quantified and compared with age-matched controls. RESULTS: Xenografts showed >75% survival with normal morphology. In the first-trimester xenografts seminiferous cord formation was initiated and in first- and second-trimester grafts normal functional development of Sertoli, Leydig and peritubular myoid cells was demonstrated using cell-specific protein markers. Grafts produced testosterone when hosts were treated with hCG (P = 0.004 versus control). Proliferation of germ cells and differentiation from gonocytes (OCT4(+)) into pre-spermatogonia (VASA(+)) occurred in grafts and quantification showed this progressed comparably with age-matched ungrafted controls. CONCLUSIONS: Human fetal testis tissue xenografts demonstrate normal structure, function and development after xenografting, including normal germ cell differentiation. This provides an in vivo system to study normal human fetal testis development and its susceptibility to disruption by exogenous factors (e.g. environmental chemicals). This should provide mechanistic insight into the fetal origins of DSDs and TDS disorders.